1997
DOI: 10.1099/00221287-143-5-1567
|View full text |Cite
|
Sign up to set email alerts
|

Use of a glycerol-limited, long-term chemostat for isolation of Escherichia coli mutants with improved physiological properties

Abstract: The evolution of Escherichia coli MG1655 mutants was followed over 126 d in a glycerol-limited chemostat at a dilution rate of 095 h'l. This corresponds to a total of 217 generations at a doubling time of 1 3 9 h. After this time, nearly 90% of the chemostat population consisted of evolved mutant strains as determined by their altered colony morphologies on plates. Two mutants were isolated that exhibited generally improved growth phenotypes in batch cultivations on glycerol, glucose or the gluconeogenic subst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 24 publications
(28 reference statements)
3
55
0
Order By: Relevance
“…Soon after the invention of the chemostat it was already established that prolonged cultivation in nutrient-limited chemostats leads to selection of spontaneous mutants with an improved affinity for the growth-limiting nutrient [52,53]. This principle, which has since been demonstrated for many micro-organisms and nutrients [40,58,72,73] was applied to improve the affinity of S. cerevisiae RWB 217 for d-xylose [44].…”
Section: Evolutionary Engineering Of D-xylose-consuming S Cerevisiaementioning
confidence: 99%
“…Soon after the invention of the chemostat it was already established that prolonged cultivation in nutrient-limited chemostats leads to selection of spontaneous mutants with an improved affinity for the growth-limiting nutrient [52,53]. This principle, which has since been demonstrated for many micro-organisms and nutrients [40,58,72,73] was applied to improve the affinity of S. cerevisiae RWB 217 for d-xylose [44].…”
Section: Evolutionary Engineering Of D-xylose-consuming S Cerevisiaementioning
confidence: 99%
“…Chemostats have been designed to select for mutants that produce enzymes with increased activity rates (10,32,33) or with altered substrate specificity (29). The latter type have been termed gain-of-function mutants.…”
mentioning
confidence: 99%
“…In addition, studies on mutative adaptation of micro-organisms in chemostat cultures have demonstrated changes in cellular activity (Novick & Szilard, 1950a;van Schie et al, 1989;Weikert et al, 1997) and morphology (Adams et al, 1985;Brown & Hough, 1965). The main challenge now resides in the identification of the molecular basis for the adaptation.…”
mentioning
confidence: 99%